Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Biologi - Uswatung Hasana; Fheny Friscasadin Ilyas; Andi Rosdiana; Nurul Magfirah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
The aim of this research is to determine the improvement in learning outcomes of students in classes X.3 and X.7 at UPT SMA Negeri 3 Maros in biology lessons by applying the Problem Based Learning learning model. The research method used is Classroom Action Research (PTK) which has been carried out in 2 cycles. The subjects taken in this research were classes X.3 and X.7 at UPT SMA Negeri 3 Maros for the 2023/2024 academic year. The data collection techniques in this research are (1) Observation, (2) Documentation, (3) Test. Based on the research results, it can be concluded that Problem Based Learning is relevant and effective for use in student and teacher activities in the teaching process in the classroom.